El juego como estrategia didáctica para mejorar la producción de cuentos escritos - Marin Sanchez, Libety Elizabeth (2021)
In the following expert suitability report it is intended to give theoretical and pedagogical _x000D_ support to the class session: The game as a didactic strategy to improve the production of _x000D_ written stories. Likewise, the academic support addresses the approaches of the linguistic of _x000D_ the text, communicative of the text, semiotic and the foundations of the theory of the text. In _x000D_ addition, it includes the concepts of writing, writing performance, the writer, its definition. _x000D_ What does the competence mean: "Write various types of texts in the mother tongue"? In _x000D_ addition, the story its definition, characteristics, types, parts and elements. On the other hand, _x000D_ for pedagogical support, cross-sectional, humanistic and cognitive approaches are addressed. _x000D_ Also, it addresses the thematic axes such as the class and its sequence, virtual classes, activity _x000D_ in the virtual classroom, strategy, virtual gamification strategies, I learn at home strategy, _x000D_ game strategy, didactics, participatory brainstorming technique, formative assessment of _x000D_ competencies related to their approach, definition, purposes, method, qualification, _x000D_ checklist, competence writes various types of texts in their mother tongue and abilities. _x000D_ Finally, this report seeks to properly implement the theoretical and pedagogical bases to _x000D_ properly develop a virtual session in this distance education given by the pandemic.